SKENARIO PEMBELAJARAN AKTIF, KREATIF, DAN MENYENANGKAN DALAM MENGEMBANGKAN KEMAMPUAN SISWA MENULIS KALIMAT MELALUI PEMANFAATAN MEDIA KARTU BERGAMBAR - Izhar, Izhar (JURNAL PESONA, 2016)
The teacher faced problems in teaching about learning scenario containedactive learning, creativity, and pleasure. There where results from someworkshops for enhancing learning quality through learning media. However,the use of learning media did not effective in elementary level. The teacherteach in conventional way in teaching their students, the example in teachingstructure, the teacher used conventional board. Wheras, some media weremade and enhanced for learning success, such as using picture card. Throughthis media, active, creative and pleasure learning with Islamic valve will become true.Keyword: Picture card, Structure.